Social dimensions of education - Tamayao, Antonio I. (Manila, Philippines : Rex Book Store, 2013)
Social Dimensions of Education is a useful textbook for prospective teachers and practicing teachers. Essentially, the book discusses human diversity in all its forms as well as the crucial role played by education in addressing problems and concerns arising from these differences. Throughout the book, the author related four major sociological theories emphasizing their analysis on human diversity. These theories include functionalism, conflict, interactionism and critical paradigms.
Chapter I The study of schools and social dimensions of education 1 -- Chapter II Sociological theories that are useful in the study of social dimensions of education 19 -- Chapter III Functions of schools 49 -- Chapter IV The four pillars of education 75 -- Chapter V Intercultural education 97 -- Chapter Vi Multicultural education 130 -- Chapter VII Inclusive education 154 -- Chapter VIII Gender and education 178 -- Chapter IX Globalization and education 201 -- Chapter X Peace education 225.
Includes bibliographical references and index.
Keywords: EDUCATION -- SOCIAL ASPECTS